Exceptionally small statistical variations in the transport properties of metal-molecule-metal junctions composed of 80 oligophenylene dithiol molecules - Xie, Zuoti; Bâldea, Ioan (Journal of the American Chemical Society, 2017)
Strong stochastic fluctuations witnessed as very broad resistance (R) histograms with widths comparable to or even larger than the most probable values characterize many measurements in the field of molecular electronics, particularly those measurements based on single molecule junctions at room temperature. Here we show that molecular junctions containing 80 oligophenylene dithiol molecules (OPDn, 1 ≤ n ≤ 4) connected in parallel display small relative statistical deviations—δR/R ≈ 25% after only ∼200 independent measurements—and we analyze the sources of these deviations quantitatively. The junctions are made by conducting probe atomic force microscopy (CP-AFM) in which an Au-coated tip contacts a self-assembled monolayer (SAM) of OPDs on Au. Using contact mechanics and direct measurements of the molecular surface coverage, the tip radius, tip-SAM adhesion force (F), and sample elastic modulus (E), we find that the tip-SAM contact area is approximately 25 nm2, corresponding to about 80 molecules in the junction. Supplementing this information with I-V data and an analytic transport model, we are able to quantitatively describe the sources of deviations δR in R: namely, δN (deviations in the number of molecules in the junction), δε (deviations in energetic position of the dominant molecular orbital), and δΓ (deviations in molecule-electrode coupling). Our main results are (1) direct determination of N; (2) demonstration that δN/N for CP-AFM junctions is remarkably small (≤2%) and that the largest contributions to δR are δε and δΓ; (3) demonstration that δR/R after only ∼200 measurements is substantially smaller than most reports based on >1000 measurements for single molecule break junctions. Overall, these results highlight the excellent reproducibility of junctions composed of tens of parallel molecules, which may be important for continued efforts to build robust molecular devices.